Weak Pb–O of confined [Pb–O4] in pyramidal sillenite-type Bi12PbO20 for enhanced electrochemical ozone production. Issue 10 (16th February 2022) - Shi, Huaijie; Feng, Ge; Li, Suiqin; Liu, Jia; Yang, Xinying; Li, Ye; Lu, Ye; Zhong, Xing; Wang, Shibin; Jianguo Wang,
Abstract : A pyramidal Bi12 PbO20 was synthesized and its application towards the electrochemical ozone production (EOP) was investigated. DFT shown that the low oxygen vacancy formation energy promotes the EOP processes. Abstract : An alternative method for producing ozone, electrochemical ozone production (EOP) is a major area of interest in the field of in situ sterilization and disinfection. However, commercial lead dioxide as a traditional anodic electrocatalyst is highly toxic and has low durability, and exploring anodic electrocatalysts with lower lead content and performance loss is challenging. Herein, a series of pyramidal sillenite-type Bi12 PbO20 materials were designed and fabricated with a hydrothermal method in which Pb was introduced to Bi2 O3 frameworks. The product, Bi12 PbO20 -3, exhibited remarkable EOP performance, with faradaic efficiency of 15.1% at 50 mA cm −2 in a neutral solution, which was almost 1.5 times that of commercial β-PbO2 . Computational simulations further demonstrated that the confined [Pb–O4 ] fragment was confined in the Bi–O bonding environment of Bi12 PbO20, the low oxygen vacancy formation energy resulted from the weak Pb–O interaction and remarkably enhanced EOP activity. Such a local confined environment plays a vital role in suppressing Pb loss, thereby accounting for the robust EOP stability. Additionally, the significant performance of the membrane electrode assembly system in the electrochemical degradation of antibiotics and pesticides implied the potential environmental application capabilities of Bi12 PbO20 .